الحركة الأباضية في عمان منذ نشأتها وحتى سقوط الإمام الأولى سنة 134هـ / 751 م - قرقش, محمد الشحات عبده (جامعة الزقازيق, 1989)
Keywords: Ibadisme – Oman

Oman: bienveillance ibadite (Le Monde, 1989)
Le conseiller du sultan Qabous 1er d'Oman fait un bond sur son siège : " Comment pouvez-vous dire que le pouvoir de Sa Majesté est absolu, du moment qu'elle est tenue d'être la première à respecter _ et faire respecter _ le Coran et la loi islamique, textes plus limitatifs que n'importe quelle Constitution ! "
Keywords: Ibadisme – Oman

Oman and ibadi Tribal Monarchic Syndrome - Saleem Khan, M.A. (Islam and the Modern Age, 1974)
Clements 1994, 152: a detailed study of Ibadhism during its medieval and modern history in Oman. Discusses the religious and political codes of Ibadhism and the history of its development in Oman and, in particular, the relationship between the elective Imamate and the interests of the Sultanate as a monarchic institution. Oman is particularly relevant to the study of Ibadhism as it is the only country with an Ibadhi majority; Ibadhism represents a much mellowed and moderate branch of the Kharijis of the first Muslim century. The Kharijis are examined to determine the development of contemporary Ibadhism, and this is followed by an account of its spread into Oman, the development of the Imamate and the struggle for political power between the Imamate and the Al Bu Said dynasty.
Keywords: Ibadisme – Oman